Kekaburan Norma Pasal 6 Undang-Undang Nomor 9 Tahun 1998 dan Rekonstruksinya melalui Tripartite Test ICCPR Pascatragedi Affan Kurniawan - Alfadri Alfadri; R Eriska Ginalita Dwi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Public order under Articles 6 and 13 of Law Number 9 of 1998 serves as the legal basis for restricting expression, yet the phrase lacks operational parameters. This vagueness opens space for subjective police interpretation of force, evidenced by repressive incidents culminating in Affan Kurniawan's death in 2025. This article analyzes the normative vagueness of public order in Law 9/1998 and formulates an ideal legal construction aligned with ICCPR standards. This research employs a normative legal methodology using both statutory and conceptual approaches. Primary legal materials include the 1945 Constitution, Law 9/1998, Law 2/2002, and Law 12/2005 ratifying the ICCPR, confronted against secondary materials comprising the Human Rights Committee's General Comment No. 37 and the Siracusa Principles. Analysis was conducted qualitatively-normatively with a descriptive-prescriptive character through deductive syllogistic reasoning that tests domestic norms against the ICCPR's tripartite test standard. The phrase public order in Article 6(d) of Law 9/1998 suffers semantic circularity and fails the lex certa principle and the prescribed-by-law test of the ICCPR tripartite test. This threshold vacuum shifts police discretion under Article 18 of Law 2/2002 from bound to unbridled discretion, evidenced by Affan Kurniawan's death and the LNHAM Joint Fact-Finding Report. Article 13A, requiring imminent life-threatening danger and ultimum remedium, effectively locks that space. These findings imply that legislators must promptly amend Law 9/1998 by embedding rigid public order parameters within its operative articles rather than the elucidation, while urging Polri to reform crowd-control regulations toward human rights-based policing that treats forced dispersal as ultimum remedium. This article's originality lies in employing the August 2025 Affan Kurniawan tragedy and the April 2026 Joint Fact-Finding Report of six national human rights institutions as up-to-date empirical evidence to test Law 9/1998's normative vagueness, while offering a concrete Siracusa Principles-based draft article absent from prior public-order scholarship.